Leader Member Exchange Terhadap Perilaku Inovatif Karyawan UMKM: Scoping Review - Lutfi Lutfi; Sopiah Sopiah (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2023)
Employee innovative behavior is very important in increasing the growth and development of MSMEs. The purpose of this study was to determine the influence of leader member exchange on the innovative behavior of MSME employees and the driving factors of leader member exchange on the innovative behavior of MSME employees. This study uses this scoping method to examine the most relevant and significant literature on leader member exchange (LMX) with related research methods. This research draws articles from several reputable national and international data bases or journals published from 2017 to 2023. The results of this study indicate that the relationship between leaders and team members in MSMEs has a significant impact on the innovative level of employees in MSMEs and the driving factors in LMX that influence the innovative behavior of MSME employees include leader support, mutual trust, open communication, recognition, and creative freedom